Children with Specific Language Impairment and Their Families: A Future View of Nature Plus Nurture and New Technologies for Comprehensive Language Intervention Strategies - Rice, Mabel L. (Seminars in Speech and Language, 2016)
Future perspectives on children with language impairments are framed from what is known about children with specific language impairment (SLI). A summary of the current state of services is followed by discussion of how these children can be overlooked and misunderstood and consideration of why it is so hard for some children to acquire language when it is effortless for most children. Genetic influences are highlighted, with the suggestion that nature plus nurture should be considered in present as well as future intervention approaches. A nurture perspective highlights the family context of the likelihood of SLI for some of the children. Future models of the causal pathways may provide more specific information to guide gene–treatment decisions, in ways parallel to current personalized medicine approaches. Future treatment options can build on the potential of electronic technologies and social media to provide personalized treatment methods available at a time and place convenient for the person to use as often as desired. The speech-language pathologist could oversee a wide range of treatment options and monitor evidence provided electronically to evaluate progress and plan future treatment steps. Most importantly, future methods can provide lifelong language acquisition activities that maintain the privacy and dignity of persons with language impairment, and in so doing will in turn enhance the effectiveness of speech-language pathologists.
Keywords: Child language impairment; specific language impairment; intervention; genetics